Differences in the response mechanism of cadmium uptake, transfer, and accumulation of different rice varieties after foliar silicon spraying under cadmium-stressed soil - Zhao, Junyang; Yu, Baoshan; Wang, Xueli; Chen, Lihong; Akhtar, Kashif; Tang, Shide; Lu, Huaming; He, Jinhua; Wen, Ronghui; He, Bing (Frontiers in Plant Science, 2023)
Most studies have shown that foliar silicon (Si) spraying can reduce the risk of rice quality safety caused by cadmium (Cd) contamination. However, it has recently been found that different rice varieties have different responses to Si. Therefore, we selected six rice varieties (YHSM, YXY1179, YXYLS, JLK1377, MXZ2, and YLY900) to compare the differences in the effects of leaf spray on Cd accumulation among different varieties. According to the change in Cd content in brown rice after Si application, the six rice varieties were divided into two types: Si-inhibited varieties (JLY1377, MXZ2, LY900, and YXYLS) and Si-stimulated varieties (WY1179 and YHSM). For Si-inhibited varieties, the Cd content of rice was reduced by 13.5%–65.7% after Si application. At the same time, the Cd content of the root, stem, leaf, panicle, and glume decreased to different degrees, the Cd content of the cell wall component increased by 2.2%–37.6%, the extraction state of Cd with strong mobile activity (ethanol-extracted and deionized water-extracted) was changed to the extraction state of Cd with weak mobile activity (acetic acid-extracted and hydrochloric acid-extracted), and the upward transport coefficient of different parts was reduced. For Si-stimulated varieties, Si application increased the Cd content of rice by 15.7%–24.1%. At the same time, the cell soluble component Cd content significantly increased by 68.4%–252.4% and changed the weakly mobile extraction state Cd to the strong mobile extraction state, increasing the upward transport coefficient of different sites. In conclusion, different rice varieties have different responses to Si. Foliar Si spraying inhibits the upward migration of Cd of Si-inhibited varieties, thereby reducing the Cd content of rice, but it has the opposite effect on Si-stimulated varieties. This result reminds us that we need to consider the difference in the effect of varieties in the implementation of foliar Si spraying in remediation of Cd-contaminated paddy fields.